The women of Wynton's : a classy 1950's mystery [large type] - Mumma, Donna (Thorndike Press large print Christian fiction series., 2025)
"Audrey Penault once led a glamorous life as a model but now works as devoted secretary to Mr. Wynton. To her fellow employees, she is too vain and uppity. Mary Jo Johnson, a wife and mother, longs to find her worth in the cosmetics department, but it may take a while for the shy housewife to discover her voice. Vivian Sheffield owns and runs the bridal salon within Wynton's. She is proud of her accomplishments and won't let anyone take them away. Gigi Woodard dislikes her job as waitress in the store's lunchroom, but she is determined not to let her secret shortcomings cause her to lose the position. These four women have much to dislike about each other, but they unanimously agree that Mr. Wynton is the best of employers and must be protected at all costs from someone who seems determined to see him gone for good. When other employee deaths occur, can the women band together to solve the murders, or will they discover it is one of their own bent on destroying Wynton's from within?"--